Effects of 4-week high intensity interval training on anaerobic capacity, repeated-sprints performance and neuromuscular function - Milioni, Fabio [UNESP] (2024)
Purpose: High-intensity long-interval training (long-HIIT; interval ≥ 1 min; intensity 85–100% of maximal oxygen uptake [V̇O2max]) is often applied for cardiorespiratory adaptations; however, long-HIIT can also challenge the anaerobic and neuromuscular systems. Therefore, this study aimed to investigate the effects of 4-week long-HIIT (11 sessions) on anaerobic capacity, repeated sprint ability (RSA), and neuromuscular function. Methods: Twenty active men (V̇O2max: 44.8 ± 5.3 mL.kg−1.min−1) performed an incremental running test (TINC), a supramaximal test consisting in running until the task failure at 115% of maximum velocity achieved in TINC (VINC) for anaerobic capacity determination, and an RSA test (2 × 6 × 35-m all-out sprints) pre- and post-HIIT. Before and after RSA, the neuromuscular function was assessed with counter movement jumps (CMJ) and knee extensors maximal isometric voluntary contractions (MVC) with femoral nerve electrical stimulation. Long-HIIT consisted of 10 × 1-min runs at 90% of VINC with 1-min recovery. Results: Long-HIIT induced significant increase in V̇O2max (P = 0.0001). Although anaerobic capacity did not change significantly, 60% of the participants improved above the smallest worthwhile change (0.2 × standard deviation of pre-HIIT). The changes in sprint performance over RSA was significantly less post-HIIT than pre (P = 0.01). RSA induced significant drop of MVC, high frequency doublet, voluntary activation and CMJ performance at pre- and post-HIIT (P < 0.01); however, the percentage of reduction from rest to fatigued conditions were not significantly altered at post-HIIT compared to Pre. Conclusions: 11 sessions of long-HIIT over 4-week improved maximal aerobic power but not anaerobic capacity, and neuromuscular function. Yet, neuromuscular fatigue was similar despite greater speeds reached during RSA.